Experimental research on desorption of ammonia decarbonization solution coupled sound wave. (September 2016) - Ma, Shuangchen; Chen, Gongda; Gao, Ran; Zhu, Sijie; Weng, Xiaoyu; Jiao, Kunling
Graphical abstract: Highlights: On self-designed experimental equipment, desorption of decarbonization liquid was studied coupling sound wave. Basic characteristic of sound wave for desorption were revealed to discuss the multi-factor influences. The effect of sound wave on NH3 escape was explored. Abstract: Currently, regeneration of decarbonization liquid and separation of pure CO2 have been realized by heating ammonia decarbonization solution. However, elevated temperature will lead to significant ammonia escape and energy consumption with traditional desorption method. Given the role of sound in degassing, sound wave was used to desorb decarbonization solution in this research. On self-designed experimental equipment, desorption of decarbonization liquid was studied coupled sound wave. To discuss multi-factor influences on sound wave desorption, basic characteristics of sound wave for desorption under different temperatures and concentrations were revealed. In the experiment, under 16 W sound wave, the desorption rate of NH4 HCO3 solution increased from 9.8% to 13.76% at 50 °C, compared with no sound wave condition; while at 70 °C, the desorption rate raised from 25.4% to 30.51%. By adding sound wave, the increment of desorbed CO2 was higher than that of escaped ammonia. The possibility of applying sound wave to desorption process in ammonia decarbonization was discussed, and a method of accelerating desorption was provided in the paper.